Development of a Water Master Plan for Tubas Governorate - Malak Jaber; Malak Mohammed; Sama Yacoub Yaish; Tasneem Saud Daraghmeh (My University, 2021)
Tubas governorate is located in the northeastern of the West Bank in Palestine, its population was about 21,431 people according to the Palestinian Central Bureau of Statistics (PCBS) for the year 2017. Tubas governorate includes several areas, for example Tayaseer, Tammun, Kardala, bardala, Ras al-Far'a, Tubas, Aqqaba, al- Aqaba. Tubas governorate extends on high plain area that slides eastward towards the Jordan Valley. It is located west of Jordan River and south of Bissan plain; the area is also rich in springs and flood streams. Tubas is one of the main agricultural areas in the West Bank and significant source for animal grazing due to soil fertility, water availability and the relatively warm weather. As increasing in the population, the demand of water will increase, otherwise climate changes and other environmental problems, lead to more consumption of water and decreasing the availability of water resources. In our graduation project, we are going to do a master plan to cover the demand in Tubas governorate during the next 20 years, evaluate and determine the future water demand in order to fill the gap of water which created by the increasing of the water demand in the future, also having a plan to fulfill the water requirements to the consumer by finding another sources or making some rehabilitation to the existing water system in Tubas Governorate. To develop this Master plan, the following steps will be followed: 1. Data collection regarding water services in Tubas Governorate. 2. Analysis of present water demand. 3. Create the concept of clusters in the Governorate. 4. Estimation of future water demand. 5. Estimation of future water gap. 6. Investigate potential future water resources. 7. Develop the needed infrastructure to convey water from proposed water resources to different clusters. The expected of this project will be a master plan for tubas governorate to falfill the water gap for the next 20 years.